163 First in vivo pretargeted pet imaging of atherosclerosis with antibodies against forms of modified lipoproteins. (4th June 2021) - Marceddu, Cinzia; Hartley, Adam; Caga-Anan, Mikhail; Pandey, Samata; Morris, Yasmin; Haskard, Dorian; Passchier, Jan; Khamis, Ramzi
Abstract : Atherosclerosis is a cardiovascular disease initiated by the deposition of Low Density Proteins (LDL) within the intima and their subsequent oxidation to (oxLDL). Currently, there are no available Positron Emission Tomography (PET) tracers for clinical imaging of atherosclerosis. LO1 and LO9 are novel antibodies that target modified low-density lipoprotein, a component of atherosclerotic plaques. Despite their high specificity for their molecular target, the use of full antibodies as PET tracers is limited due to their long circulation time. Pretargeted labelling of antibodies overcomes this limitation by decoupling the antibodies' slow pharmacokinetics from the half-life of the radioisotope, injecting the two components separately and facilitating their use as tracers.The methodology requires a trans-cyclooctene (TCO) conjugation to the antibody, followed by the selective in vivo reaction with a radiolabelled tetrazine (Tz) injected after the conjugated antibody has accumulated on target and partially cleared form the blood.The components necessary for the pretargeted PET imaging of atherosclerosis were prepared and characterised. The radiolabelle tetrazine [18F]FpyTz was prepared and purified with a radiochemical yield of 10.5% and a radiochemical purity <99%. In addition, a near-infrared (NIRF) emitting tetrazine Tz-VT was also synthesized to mimic the behavior of the radiolabeled analogues in some in vitro and ex vivo tests.Conjugation of LO9 and LO1 yielded LO9-TCO and LO1-TCO, respectively. Aortic root sections from LDL-R-/- mice fed a high-fat diet for 14 weeks were exposed to LO9, LO1, LO9-TCO and LO1-TCO respectively, followed by Tz -VT, and examined using fluorescent microscopy. The stained sections exposed to LO9-TCO or LO1-TCO and Tz showed areas of positive signal along the plaque edges a representative example obtained using LO9-TCO is depicted in figure, while control slides exposed to LO9 or LO1 showed no signal. Ldlr-/- mice fed a high-fat diet for 22 weeks were injected with the modified antibodies first and with the radiolabelled tetrazine after 72h. PET/CT studies and Ex vivo biodistribution studies were via γ-counter were performed. Additionally, PET/CT and ex vivo biodistribution studies were performed with directly labelled antibodies LO1-89Zr and LO9-89Zr to enable comparison. Animals injected with LO1 and LO9 showed a higher aorta uptake when compared with the control antibody. Analysis of PET images of pretargeted antibodies showed co-localisation of LO9 and LO1 at bifurcations of the aorta. The first studies of in vivo pretargeted PET detection of atherosclerosis were performed, our studies successfully demonstrated pretargeting of native low-density lipoprotein within atherosclerotic plaques in mice, in-vivo and ex-vivo using plaque specific antibodies. Conflict of Interest: none